2014
DOI: 10.1371/journal.pone.0109246
|View full text |Cite|
|
Sign up to set email alerts
|

Angiopoietin-2 and Angiopoietin-2/Angiopoietin-1 Ratio as Indicators of Potential Severity of Plasmodium vivax Malaria in Patients with Thrombocytopenia

Abstract: IntroductionAngiogenic factors such as angiopoietin 1 (Ang-1) and angiopoietin 2 (Ang-2) are biomarkers produced during activation and dysfunction of the vascular endothelium in several infectious diseases. The aim of this study was to determine the serum levels of Ang-1 and Ang-2 and to establish their relationship with the main indicators of worst-case prognosis in patients with P. vivax malaria.MethodsThis is a retrospective case-control study nested within a cohort of symptomatic malaria patients. A potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
29
0
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 50 publications
10
29
0
8
Order By: Relevance
“…In a retrospective cohort, patients who died from malaria had lower platelet counts in comparison to those with less severe disease (3). Moreover, P. vivax malaria patients with thrombocytopenia showed higher levels of markers of endothelial cell (EC) activation compared to those with normal platelet counts (4) and some grade of platelet activation has been reported during the disease (5). Together, these reports point out to a significant role of platelets in the pathophysiology of malaria.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective cohort, patients who died from malaria had lower platelet counts in comparison to those with less severe disease (3). Moreover, P. vivax malaria patients with thrombocytopenia showed higher levels of markers of endothelial cell (EC) activation compared to those with normal platelet counts (4) and some grade of platelet activation has been reported during the disease (5). Together, these reports point out to a significant role of platelets in the pathophysiology of malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies with PCR confirmed P. vivax malaria reported parasite density. Of these, one study showed a higher parasite density among patients with severe thrombocytopaenia in P. vivax malaria than in those with either mild thrombocytopaenia or no thrombocytopaenia ( P = 0.524) [ 26 ]. The remaining 2 studies [ 21 , 38 ] qualitatively reported almost the same P. vivax parasite density in patients with thrombocytopaenia and those without thrombocytopaenia.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies of severe and cerebral malaria (both falciparum and vivax) in children and adults treated with antimalarial drugs have documented endothelial dysfunction: decreased plasma levels of angpt-1, increased levels of angpt-2 and increased angpt-2/angpt-1 ratios (196)(197)(198)(199)(200)(201)(202)(203). Other findings include elevated levels of several pro-inflammatory cytokines and chemokines and other biomarkers indicating endothelial [vascular/intercellular adhesion molecule-1 (VCAM-1/ICAM-1), endothelial selectin (E-selectin)), coagulation (thrombomodulin) and complement (C5a) activation.…”
Section: Implications For Treating the Host Response To Other Acute Imentioning
confidence: 99%